The heterogeneous response of the stock market to emission allowance price: evidence from quantile regression - Huiming Zhu; Yiding Tang; Cheng Peng; Keming Yu (Carbon Management, 2018)
This paper investigates the effects of the European Union Emission Allowance (EUA)’s price on European carbon-intensive industries’ stock returns based on daily data from April 25, 2005 to July 24, 2017. Utilizing a multifactor market model specification and a panel quantile regression approach, the study tests whether the influences of the EUA price on the stock market are heterogeneous and asymmetric concerning each phase. The results show that a significant negative impact of the EUA price on the stock market is found in the middle- and high-return markets during Phases I and III, whereas in Phase II, the impacts are positive. Additionally, no asymmetric feature of the carbon market effect is shown in Phases I and III, but it shows a strong asymmetric effect across quantiles during Phase II. Some factors such as allocation rules and macroeconomic stability may cause this dissimilarity.